Effect of Cochlear Nerve Electrocautery on the Adult Cochlear Nucleus. Issue 4 (April 2015) - Iseli, Claire E.; Merwin, William H.; Klatt-Cromwell, Cristine; Hutson, Kendall A.; Ewend, Matthew G.; Adunka, Oliver F.; Fitzpatrick, Douglas C.; Buchman, Craig A.
<x xml:space="preserve">Abstract</x> Hypothesis Electrocauterization and subsequent transection of the cochlear nerve induce greater injury to the cochlear nucleus than sharp transection alone. Background Some studies show that neurofibromatosis Type 2 (NF2) patients fit with auditory brainstem implants (ABIs) fail to achieve speech perception abilities similar to ABI recipients without NF2. Reasons for these differences remain speculative. One hypothesis posits poorer performance to surgically induced trauma to the cochlear nucleus from electrocautery. Sustained electrosurgical depolarization of the cochlear nerve may cause excitotoxic-induced postsynaptic nuclear injury. Equally plausible is that cautery in the vicinity of the cochlear nucleus induces necrosis. Methods The cochlear nerve was transected in anesthetized adult gerbils sharply with or without bipolar electrocautery at varying intensities. Gerbils were perfused at 1, 3, 5, and 7 days postoperatively; their brainstem and cochleas were embedded in paraffin and sectioned at 10 μm. Alternate sections were stained with flourescent markers for neuronal injury or Nissl substance. In additional experiments, anterograde tracers were applied directly to a sectioned eighth nerve to verify that fluorescent-labeled profiles seen were terminating auditory nerve fibers. Results Cochlear nerve injury was observed from 72 hours postoperatively and was identical across cases regardless of surgical technique. Postsynaptic cochlear nucleus injury was not seen after distal transection of the nerve. By contrast, proximal transection was associated with trauma to the cochlear nucleus. Conclusion Distal application of bipolar electrocautery seems safe for the cochlear nucleus. Application near the root entry zone must be used cautiously because this may compromise nuclear viability needed to support ABI stimulation.